The financial performance before and after mergers and acquisitions of State-owned Islamic banks in Indonesia - Mulfi Rahman; Chandra Setiawan; Chongmi An (President University, 2022)
This study aims to explore which variables have the most significant influence on Return on Assets (ROA) and differences in financial performance after Mergers and Acquisitions (M&A) of Sharia banks in Indonesia. By using purposive sampling and panel data analysis, this study uses three samples, namely PT Bank Rakyat Indonesia Syariah (BRIS), PT Bank Negara Indonesia Syariah (BNIS) an d PT Bank Syariah Mandiri (BSM). 77 secondary data have been collected from the financial statements between periods 2015Q1-2020Q4 for the timeline before the M&A and 2021Q1-2021Q2 for the timeline after. This study uses several analytical methods, namely Mann-Whitney Test, classical assumptions, multiple linear regression, and hypothesis testing. Based on research conducted prior to the M&A, the results show that the Capital Adequacy Ratio (CAR) and Operating Expense to Operating Income (OEOI) have a significant effect on ROA. Meanwhile, Non-Performing Financing (NPF), Finance to Deposit Ratio (FDR), and Third-Party Fund have no significant effect on ROA. Simultaneously, the five variables account for 72.80% of the significant change in ROA. The capital adequacy ratio and operating expense to operating income have been identified as having the most significant impact. In terms of the direction of change before and after the M&A, ROA has significantly increased after the M&A, implying that the M&A had a positive impact on Sharia banks in Indonesia.